Kontribusi pengalaman praktik kerja industri dan Kemampuan soft skills terhadap kesiapan kerja Siswa kelas xII akuntansi SMK Negeri 1 Klaten Tahun ajaran 2016/2017 - Widyastanti, Safitri, Drs. Djoko Suwandi, SE., M.Pd (2017)
This research aim to determine 1) the contribution of industrial work practice experience toward work readiness students class XII Accounting in SMK Negeri 1 Klaten academic year 2016/2017, 2) the contribution soft skills ability toward work readiness students classs XII Accounting in SMK Negeri 1 Klaten academic year 2016/2017, 3) the contribution of industrial work practice experience and soft skills ability toward work readiness students class XII Accounting in SMK Negeri 1 Klaten academic year 2016/2017. This research employed the ex-post facto design in which the conclusion of the study was acquired based on statistic result where the result was laid out in numbers. The population which was used was class XII Accounting SMK Negeri 1 Klaten academic year 2016/2017, amount to 145 students in which 102 students were taken to be the sample. This study was using random sampling techniques with simple random sampling method. For collecting data techniques, the researcher used questionnaire and documentation method. Previously, the questionnaire method had been through trial run by using validity test and reability test. Data analysis techniques which was used multiple regression, t test, F test, effective contribution and relative contribution. The result of this research using regression analysis was obtained regression formula : Y=5,339 + 0,480X1 + 0,693X2 + e. The result concluded 1) Industrial work practice experience have positive contribution toward work readiness students is 12,59%, 2) Soft Skills ability have contribution toward work readiness students is 49,71%, 3) Indsutrial work practice experience and soft skills ability same have positive contribution toward work readiness students is 62,3% and the rest 37,70% was influenced by other variables which were not included in this research.